Analise de Desempenho e ?? Consumo de Energia da Fus??o de Informa????es de Sensoriamento Espectral - Aguiar , H??liton Silva (2022)
In addition to traditional performance metrics in the context of spectrum sensing in cognitive radio networks, energy consumption has received a lot of attention, as it is a limited resource. In this document, the performance of spectrum sensing based on the energy detector and also the energy consumption of the network is analyzed in three cooperative sensing modes: data fusion, decision fusion and hybrid fusion. The presented computer simulation results make use of a realistic model in terms of the location and mobility of the terminals, and of the cluster formation rule in the hybrid fusion mode. Firstly, a mobility mode with uniform distribution is used for performance analysis and energy consumption. Then, a model that aims to simulate the mobility of a real terminal was adapted to a circular area to perform the analyses considered in the uniform model. For the formation of clusters, a method is adopted that takes into account the positioning of the mobile terminals, aiming it improving the energy consumption.